ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN IBU MENYUSUI YANG BEKERJA TIDAK MEMBERIKAN ASI EKSKLUSIF - Tri Utami Sari; Cipta Pramana; Sumarmi (LPPM Universitas Abdurrab, 2026)
Background: Exclusive breastfeeding coverage globally is still low, at around 38%, so it has not reached the global target of 50% by 2025. In Indonesia, exclusive breastfeeding coverage increased from 69.70% in 2022 to 70.01% in 2023. In Central Java it increased from 79.06% to 80.02%, while in Semarang City it reached 81.3%. However, the coverage of exclusive breastfeeding in the working area of the Krobokan Health Center is only 33.8%, so that 66.2% of babies have not received exclusive breastfeeding. As many as 52% of mothers who do not succeed in providing exclusive breastfeeding are working mothers. This study aims to analyze the relationship between parity, knowledge, family support, availability of breastfeeding facilities, supervisor support, and peer support with the non-achievement of exclusive breastfeeding in working mothers in the working area of the Krobokan Health Center, Semarang City. Methods: A correlational analytical study with a case control design on 79 working mothers who had babies aged 6–12 months using purposive sampling techniques. The research will be carried out in November-December 2025. Data analysis used Chi-square test and binary logistics regression. Results: There was a correlation between parity (p=0.026; OR=3.157), knowledge (p=0.029; OR=3.059), availability of breastfeeding facilities (p=0.017; OR=3.375), family support (p=0.001; OR=5.600), support from the employer (p=0.036; OR=2.933), and peer support (p=0.033; OR=2.986) with the absence of exclusive breastfeeding in working mothers. Multivariate analysis showed that family support was the most dominant factor (p=0.001; OR=26,678). Conclusions: Parity, knowledge, family support, availability of breastfeeding facilities, employer support, and peer support were associated with the non-achievement of exclusive breastfeeding in working mothers, with family support as the most dominant factor